Ragnar Frisch's contribution to business cycle analysis - Olav Bjerkholt (University of Oslo, Department of Economics, 2007)
Business cycle analysis, i.e. investigations into the more or less regular fluctuations in economic activity, emerged around the mid-nineteenth century. During Ragnar Frisch's formative years as a young economist the field came to the centre of attention. Frisch was highly concerned about the inability of modern economies in the midst of plenty to prevent economic fluctuations from playing havoc with the livelihood of millions. He first directed his attention towards methods for analysing time series data and increasingly shifted it to the question of the nature of a proper theoretical explanation of economic fluctuations. Thus Frisch's orientation and contribution was not so much business cycle analysis in the substantive sense, understood as explaining why and how economic activities varied cyclically, but the appropriate methods for analysing and explaining cycles. He is best known for the model he presented in his Propagation and Impulse essay in the festschrift for Gustav Cassel (Frisch, 1933b). It became Frisch's most ambitious research project before World War II, but the intended main publications from the project never appeared. Due to Frisch's incomplete publication of his work the Propagation and Impulse essay may have been interpreted with too much emphasis on the content and properties of the macroeconomic model Frisch presented. His real message was to demonstrate his overall paradigm for macro analysis in economics. This article looks in more detail at the genesis of the propagation and impulse model. The presentation is non-technical and includes some biographical details.
Keywords: A10; 330; Ragnar Frisch; business cycle analysis; propagation and impulse; Ökonomen; Dogmengeschichte; Konjunkturforschung; Wachstumstheorie; Wachstumszyklus